Penyampaian Aspek Keperilakuan Akuntansi dalam Kurikulum - Drajat Armono (Jurnal Aplikasi Bisnis, 2017)
Behavioral Accounting as the subject began to be implemented in some universities. However there are some differences of opinin both the delivery and the willingness to put it into the college curriculum. This paper aims to provide an alternative way of delivering the behavioral aspects of accounting if the material is incorporated into the curriculum. Authors reasoned take the title as given that all of science will lead to behavioral in their respective fields. In other words, all areas would ultimately lead to behavioral aspects to better understand the essence of the exiting knowledge in the field.Accounting as a branch of science that need to understand the meaning behind each decision made by both individuals and organizations. By developing behavioral aspects, allows accounting to be learned up to the highest level in the world of education. This paper also provides an alternative behavioral development in the accounting curriculum, namely (1) Behavioral Accounting incorporated as a special course in the accounting curriculum, and (2) behavioral aspects or components incorporated as an integral part of any accounting course.